ENTROPY BASED EVALUATION OF THE IMPACT OF EDUCATION ON ECONOMIC DEVELOPMENT - Mykhailova, Yelyzaveta; Savina, Nataliia; Lytvynenko, Volodymyr; Mykhailov, Stanislav (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
In contemporary economic landscapes, effective managerial decision-making requires serious justifications often facilitated by information technologies. The article proposes the application of the foundational principles from information theory and entropy to determine the correlation between education and economic development. This research employs entropy methodology to explore the correlations and implications of these multifaceted domains, drawing insights from a range of global indices. By analyzing data from indices such as the Human Development Index, we investigate the relationship between average years of education and entropy values, shedding light on the diversity and standardization of human capital systems across nations. Moreover, economic indexes, encapsulating factors such as economic freedom and innovation, provide critical insights into the vibrancy and resilience of national economies. Through the lens of the Global Innovation Index, we explore how countries with higher levels of economic freedom and innovation efficiency exhibit less diversity in economic approaches and innovation strategies, leading to a reduction in entropy values. By examining entropy values in conjunction with innovation indicators, such as research and development expenditure and patent applications, we uncover patterns and trends indicative of the diversity or standardization of innovation strategies across countries. Additionally, cybersecurity emerges as a critical dimension of national security and resilience, with implications for economic well-being and societal trust. Through the National Cybersecurity Index, we assess the level of diversity and uncertainty in cybersecurity landscapes, highlighting the importance of robust cybersecurity measures in safeguarding against emerging threats and reducing entropy values. Ultimately, this research contributes to the discourse on sustainable development and resilience in an interconnected world. By identifying specific challenges and opportunities within education, economy, innovation, and cybersecurity domains, it facilitates informed decision-making and strategic interventions to promote inclusive growth and societal well-being on a global scale.